Pengaruh Likuiditas dan Leverage Terhadap Profitabilitas pada Perusahaan Manufaktur Sub Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia Periode 2019-2024 - Angga Mauliza; Abu Hasan Makmun; Muzakir Muzakir (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of liquidity and leverage on profitability in manufacturing companies listed on the Indonesia Stock Exchange for the period 2019–2024. In the business and investment world, profitability is one of the main indicators used to assess a company's financial performance as well as its ability to generate sustainable profits. Manufacturing companies, as one of the sectors that play an important role in the national economy, are required to manage their resources effectively, particularly in terms of managing current assets and capital structure. However, the phenomenon shows that the profitability of manufacturing companies has fluctuated, especially during the COVID-19 pandemic, thus further analysis is needed to examine the factors affecting it. The method used in this study is a quantitative approach with descriptive analysis and multiple linear regression. The data used are secondary data in the form of financial statements of manufacturing companies obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id). The variables in this study consist of liquidity measured by the Current Ratio (CR), leverage measured by the Debt to Equity Ratio (DER), and profitability measured by Return on Assets (ROA). The results of the study indicate that partially, liquidity has a positive and significant effect on profitability, and leverage also has a positive and significant effect on profitability. Simultaneously, liquidity and leverage have a significant effect on the profitability of manufacturing companies with a significance value below 0.05. This indicates that the company's ability to manage current assets and capital structure simultaneously plays an important role in increasing profitability.